Response to two Janus kinase inhibitors in a boy with SAVI during 2-year follow-up: case report and literature review - Yiting Chen; Yiting Chen; Wenhe Zang; Haoyuan Zhong; Xianqin Deng; Wenting Zhong; Wenting Zhong; Lianyu Wang; Lianyu Wang; Xinying Chen; Xinying Chen; Xinying Chen (Frontiers in Immunology, 2025)
STING-associated vasculopathy with onset in infancy (SAVI) represents an identified rare type I interferonopathy, triggered by gain-of-function mutations in the STING1 gene. It is characterized by early-onset systemic inflammation, cutaneous vasculopathy, pulmonary involvement, and recurrent bacterial infections. When conventional treatments prove ineffective in managing clinical symptoms, a high index of suspicion and prompt genetic testing become pivotal in considering the potential therapeutic role of Janus kinase (JAK) inhibitors, with ruxolitinib and tofacitinib emerging as promising treatment options. Here, we present a case involving a patient with severe lung manifestations of SAVI, treated initially with tofacitinib and later switched to ruxolitinib due to inadequate response. During a 24-month follow-up period, while symptoms stabilized under ruxolitinib, chest computed tomography (CT) scans revealed progressive changes. This case report offers valuable insights into the use of JAK inhibitors in a patient with SAVI. It illustrates the complexities of managing such cases and underscores the need for continued investigation into novel therapeutic approaches.